CRISPR/Cas9‐mediated whole genomic wide knockout screening identifies mitochondrial ribosomal proteins involving in oxygen‐glucose deprivation/reperfusion resistance. Issue 16 (2nd July 2020) - Guan, Xinjie; Zhang, Hainan; Qin, Haiyun; Chen, Chunli; Hu, Zhiping; Tan, Jieqiong; Zeng, Liuwang
Abstract: Recanalization therapy by intravenous thrombolysis or endovascular therapy is critical for the treatment of cerebral infarction. However, the recanalization treatment will also exacerbate acute brain injury and even severely threatens human life due to the reperfusion injury. So far, the underlying mechanisms for cerebral ischaemia‐reperfusion injury are poorly understood and effective therapeutic interventions are yet to be discovered. Therefore, in the research, we subjected SK‐N‐BE(2) cells to oxygen‐glucose deprivation/reperfusion (OGDR) insult and performed a pooled genome‐wide CRISPR (clustered regularly interspaced short palindromic repeats)/Cas9 (CRISPR‐associated protein 9) knockout screen to discover new potential therapeutic targets for cerebral ischaemia‐reperfusion injury. We used Metascape to identify candidate genes which might involve in OGDR resistance. We found that the genes contributed to OGDR resistance were primarily involved in neutrophil degranulation, mitochondrial translation, and regulation of cysteine‐type endopeptidase activity involved in apoptotic process and response to oxidative stress. We then knocked down some of the identified candidate genes individually. We demonstrated that MRPL19, MRPL32, MRPL52 and MRPL51 inhibition increased cell viability and attenuated OGDR‐induced apoptosis. We also demonstrated that OGDR down‐regulated the expression of MRPL19 and MRPL51 protein. Taken together, our data suggest that genome‐scale screening with Cas9 is a reliable tool to analyse the cellular systems that respond to OGDR injury. MRPL19 and MRPL51 contribute to OGDR resistance and are supposed to be promising targets for the treatment of cerebral ischaemia‐reperfusion damage.